Post-endoscopy esophageal adenocarcinoma and root cause analysis in Auckland, New Zealand - Shin, Seong; Kang, Dongyeon; Walmsley, Russell S (Endoscopy International Open)
Background and study aims: Post-endoscopy esophageal adenocarcinomas (PEEC) challenge timely diagnosis of esophageal adenocarcinomas (OAs). This study aimed to determine prevalence of PEECs in Auckland region and elucidate the most plausible causes through a root-cause analysis framework. Patients and methods: OA cases diagnosed in Auckland from 2013 to 2022 were retrieved from the New Zealand Cancer Registry (NZCR). Electronic clinical data were collected via the Regional Clinical Portal software. The primary outcome was PEEC prevalence, defined as OA diagnosed 6 to 36 months following an esophagogastroduodenoscopy (EGD) that failed to detect the cancer. Identified PEECs were classified into six categories. Results: Among 633 OA cases, 45 (7.1%) were PEECs. A higher prevalence of PEEC was observed in patients with Barrett’s esophagus (BE) (18.1% vs 2.7%), undergoing surveillance EGDs (52.6% vs 3.6%) and with early-stage cancers. Root-cause analysis delineated the PEEC causes, classified as follows: A (17.8%): lesion was identified, endoscopic assessment was adequate, follow-up was appropriately planned and executed, yet PEEC developed; B (17.8%): follow-up was delayed due to administrative factors; C (22.2%): follow-up decisions were inappropriate; D (22.2%): inadequate endoscopic assessment; E (11.1%): lesion was unidentified despite adequate assessment; and F (8.9%): lesion was unidentified and assessment was inadequate. Categories B, C, D, and F comprised 71.1% of cases deemed potentially avoidable. Conclusions: Auckland’s PEEC prevalence aligns with international post-endoscopy upper gastrointestinal cancer rates. Root-cause analysis underscores that a significant proportion of PEECs may be preventable with improved clinical practice.